Measuring the satisfaction of residents of Mehregan township of Mashhad from sustainable housing perspective - Daime Kar, Mohammad Reza; Ahmadian, Mohammad Ali; Alizadeh, Katayoun; Hataminezhad, Hossein (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Demographic developments in Mashhad and surrounding rural areas which are now considered urban break points It is well established that these areas have become centers of attraction for low-income immigrants who intend to migrate to Mashhad, as well as low-income urban strata that have previously lived in Mashhad. Since all four types of worn-out urban textures, including urban heritage, non-urban, marginal and rural urban textures, are the middle and lower decay habitats, "The 5000 unit project of Mehregan Town of Mashhad" has played an important role in the physical and functional organization of these tissues and responding to the needs of the poor. In view of the above, and several years after the project was inaugurated, the superstructure and infrastructure problems of the project are the subject of research in this research. The research method in this study was descriptive-analytical and applied. According to the number of households in the city that formed the statistical population of the study, and based on Cochran's formula, the sample population was 366 persons. Also, Delphi method has distributed 32 questionnaires to expert experts. Descriptive and inferential statistical analysis of completed questionnaires and experts has been done with the help of nonparametric and parametric statistical methods. The results of field surveys showed that the observed frequency of low-satisfaction residents was 222 and above all, so it is safe to say that 95% of respondents are not satisfied with their residence in Mehregan town. It is believed that the residential units constructed in Mehregan town of Mashhad have poor compliance with the standards and standards of sustainable housing.